Extant morphotypes of Distephanus speculum (Silicoflagellata) from the Australian sector of the Southern Ocean: Morphology, morphometry and biogeography - MALINVERNO, ELISA (Marine Micropaleontology, 2010)
Extant morphotypes of Distephanus speculum (Ehrenberg 1839) Heckel 1887, analysed from a latitudinal transect of surface water samples and one hydrological station in the Southern Ocean, display a distinct biogeographic distribution pattern. Morphometric analyses performed on a total of 250 specimens from 12 selected samples reveal that some morphotypes, separated through secondary morphological characters, can also be separated on a size basis. Small-sized specimens include D. speculum speculum, D. speculum var. monospicatus (var. nov.) and D. speculum bispicatus; medium-sized specimens are represented by D. speculum f. coronata and D. speculum minutus - coronatid and large-sized specimens correspond to D. speculum group B of Tsutsui et al. (2009).The ecological value of the morphological and morphometric characters is discussed here in relation with the latitudinal distribution of the morphotypes. A new taxon, D. speculum var. monospicatus (var. nov.), is described. © 2010 Elsevier B.V.